HUBUNGAN PERILAKU MENCUCI DENGAN KONTAMINASI TELUR NEMATODA USUS PADA SAYURAN KUBIS (Brassica oleracea) PEDAGANG PECEL LELE DI KELURAHAN WARUNGBOTO KOTA YOGYAKARTA - Suryani, Dyah (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2012)
Background: Vegetables can be eaten whole or in part in fresh or raw (fresh vegetables) or cooked. Vegetables is beneficial for health because they contain relatively high nutritional vita-mins and minerals, one of which is cabbage or cabbage. Cabbage has dicucipun may still con-tain pests and diseases, such as nematodes. Due to poor washing. In Indonesia, the nematode intestine is still a public health problem is Ascaris lumbricoides, hookworm and Trichuris trichi-ura. Soil, vegetables and water is an important transmission media, a growing number of eggs found in the sources of contamination (vegetable, soil, etc.) will be accompanied by an increase in the degree of endemics. Advanced Research goal is to look at the relationship between the behavior of washing vegetables with intestinal nematode egg contamination in vegetable cab-bage merchant in the Village of catfish pecel Warungboto city of Yogyakarta. This study has the benefit of policy making in disease eradication wormy and add information that is consumed raw vegetables can infect humans through the intestinal nematode egss Atlanta. Methods: The study was observational analytic study with cross sectional research design. Washing behavior obtained by direct observation to guide traders with check list. Vegetable sprouts are used as raw vegetables (vegetables) contained on the merchant pecel Warungboto catfish in the Village of Yogyakarta. Wash solution for the deposition of intestinal nematode eggs used was 0.2% NaOH solution. Examination conducted by using techniques of direct ex-amination and then examined under a microscope. Data examination of the behavior of the cabbage and wash vegetables presence or absence of intestinal nematode eggs, species of intestinal nematode eggs. Data were analyzed using univariate and bivariate analysis with chi square analysis. Examination results: The results of this examination showed that of 26 respondents found 16 respondents (61.5%) had not properly washing vegetables and 10 respondents (38.5%) had a good washing vegetables. Bivariate analysis for the behavioral relationship with the intestinal nematode egg contamination in vegetable cabbage is a value sig = 0.35 is greater than the value of alpha (? = 0.05) and RP = 3.125 (95% CI: 0.424 to 23.007). Conclusion: There were no relationship between the behavior of washing vegetables with egg contamination in vegetable cabbage worms in the shop pecel catfish Yogyakarta Village Wa-rungboto 2011. Keywords: Behavior, vegetables cabbage (Brassica oleracea), intestinal nematode eggs.